Bandido: the life and times of Tiburcio Vasquez - Boessenecker, John (University of Oklahoma Press, 2010)
Sons of the conquistadores -- In old Monterey -- A boyhood among bandits -- The Roach-Belcher feud -- He never showed the white feather -- The big break -- Bandido -- In the saddle with Juan Soto -- Stagecoach robber -- Shootouts and lynchings -- Ride the high country -- "I'm a ranger, by God!" -- The tres pinos tragedy -- Pursuit and betrayal -- Raiders of the San Joaquin -- Harry Morse tries his hand -- Manhunt in Los Angeles -- Dead or alive -- The murder trial -- To die game -- Epilogue: buried treasure, social banditry, and other myths